Expanding the molecular spectrum of pathogenic SHOC2 variants underlying Mazzanti syndrome. Issue 16 (26th March 2022) - Motta, Marialetizia; Solman, Maja; Bonnard, Adeline A; Kuechler, Alma; Pantaleoni, Francesca; Priolo, Manuela; Chandramouli, Balasubramanian; Coppola, Simona; Pizzi, Simone; Zara, Erika; Ferilli, Marco; Kayserili, Hülya; et al.
Abstract: We previously molecularly and clinically characterized Mazzanti syndrome, a RASopathy related to Noonan syndrome that is mostly caused by a single recurrent missense variant (c.4A > G, p.Ser2Gly) in SHOC2, which encodes a leucine-rich repeat-containing protein facilitating signal flow through the RAS-mitogen-associated protein kinase (MAPK) pathway. We also documented that the pathogenic p.Ser2Gly substitution causes upregulation of MAPK signaling and constitutive targeting of SHOC2 to the plasma membrane due to the introduction of an N -myristoylation recognition motif. The almost invariant occurrence of the pathogenic c.4A > G missense change in SHOC2 is mirrored by a relatively homogeneous clinical phenotype of Mazzanti syndrome. Here, we provide new data on the clinical spectrum and molecular diversity of this disorder and functionally characterize new pathogenic variants. The clinical phenotype of six unrelated individuals carrying novel disease-causing SHOC2 variants is delineated, and public and newly collected clinical data are utilized to profile the disorder. In silico, in vitro and in vivo characterization of the newly identified variants provides evidence that the consequences of these missense changes on SHOC2 functional behavior differ from what had been observed for the canonical p.Ser2Gly change but converge toward an enhanced activation of the RAS-MAPK pathway. Our findings expand the molecular spectrum of pathogenic SHOC2 variants, provide a more accurate picture of the phenotypic expression associated with variants in this gene and definitively establish a gain-of-function behavior as the mechanism of disease.